Phosphorus (from Different Phosphorus Sources) Utilisation in Piglets, and the Effect of the Addition of Phytase into the Feedstuff - Gundel, János; Regiusné Mőcsényi, Ágnes; Hermán, Istvánné; Huszár, Szilvia; Votisky, Lászlóné; Szelényiné Galántai, Marianne; Fébel, Hedvig (Acta Agraria Debreceniensis, 2002)
The experiments were carried out in a 2x2 factorial treatments with three replicates, and were completed with 32P phosphorus metabolism measurement. Hungarian Large White x Dutch Landrace growing pigs with 15–18 kg starting live weight were involved in the experiment.The experimental scheme was the following:Diet consisted of maize and extracted soybean meal. Both components have high phytase content and low phytase activity. 1/a animals received their P-supply according to their needs and 1/b animals got 10% less than their actual P-need in the first part of the experiment.In the second part of the experiment both groups (2/a, 2/b) received identical P-supply and 500FTU/kg P supplementation. Apart from P- and phytase-supplementation, the piglets’ diet was identical.Total P digestibility was 52% without phytase supplementation, which increases by 4% when P was added according to need and by 12% increase of decreased P-supply. Digestibility of nutrients somewhat increased as effect of phytase supplementation. According to the results of 32P experiments, inorganic P digestibility of MCP was 82–90.8%, which decreases to 73.4–87.2% in case of phytase supplementation.Parallel with tendency, native P digestibility of the diet was 31.5–32.2%, which increased to 42.5–54.5% in the case of phytase supplementation.Results support the that inorganic P input can be decreased by phytase supplementation and as a consequence P output, the concept and environmental pollution can at the some time be decreased.